SAE Technical Paper Series 2018
DOI: 10.4271/2018-01-0191
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Gasoline Surrogate (Toluene/n-Heptane/iso-Octane) Chemical Kinetic Model for Compression Ignition Simulations

Abstract: Toluene primary reference fuel (TPRF) (mixture of toluene, iso-octane and heptane) is a suitable surrogate to represent a wide spectrum of real fuels with varying octane sensitivity. Investigating different surrogates in engine simulations is a prerequisite to identify the best matching mixture. However, running 3D engine simulations using detailed models is currently impossible and reduction of detailed models is essential. This work presents an AramcoMech reduced kinetic model developed at King Abdullah Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…In our previous study [15], a three component TPRF kinetic model with 80 species and 414 reactions (including NOx) is developed and fully validated. Here, the goal is to develop a fourcomponent TPRF-E model with a smaller number of species and reactions for multi-dimensional CFD applications.…”
Section: Model Reduction Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study [15], a three component TPRF kinetic model with 80 species and 414 reactions (including NOx) is developed and fully validated. Here, the goal is to develop a fourcomponent TPRF-E model with a smaller number of species and reactions for multi-dimensional CFD applications.…”
Section: Model Reduction Approachmentioning
confidence: 99%
“…First, a skeletal ethanol sub-mechanism was added to the recently developed TPRF model in [15], which was generated manually, which includes three more species: C2H5OH, SC2H4OH and CH3CHO, and the relevant high temperature reaction classes (H-atom abstraction and radical beta-scission).…”
Section: Model Reduction Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Kodavasal et al [42] showed that a finer grid might be needed to reach grid independent solution for reacting cases; however, the current grid was considered sufficient for the objectives of this study which was mainly examining the effect of fuels' properties on the engine performance. The reduced PRF chemical kinetic models developed by KAUST (64 species and 376 reactions) was used in this work [64]. The prediction of NOx emissions was performed using the extended Zedovich thermal NOx model.…”
Section: /19/2016mentioning
confidence: 99%